Clinical Features of Pulmonary Tuberculosis Patients Performing Molecular Rapid Test at Jakarta Islamic Hospital Cempaka Putih - Shabrina, Fida Alia; Rayhana, Rayhana; Wahyuni, Tri (Muhammadiyah Medical Journal, 2025)
Background: Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. This germ has a dormant phase, which causes the healing process to take a long time, thereby increasing the risk of discontinuing drug consumption in TB patients. This has resulted in resistance to several types of anti-tuberculosis drugs, one of which is Rifampicin, a first-line drug in TB treatment. Rifampicin-resistant TB (RR-TB) requires rapid and precise diagnosis and treatment, namely the PCR method using the GeneXpert tool. Purposes: To find out the clinical features of pulmonary tuberculosis patients performing TCM GeneXpert at the Jakarta Islamic Hospital Cempaka Putih in January – June 2022. Methods: This study employs a descriptive observational method, which describes a clinical feature based on secondary data (medical records) from adult pulmonary TB patients undergoing TCM at RSIJ Cempaka Putih. Results: Among patients examined by Molecular Rapid Test, 64 individuals (59.3%) were MTB-detected, and among them, 12 individuals (18.8%) had rifampicin resistance. The highest positivity value from the results of MTB-detected was MTB-Medium Detected, namely 11 people (10.2%). The most common clinical symptom in pulmonary TB patients was cough with phlegm, which was 67 people (62%), and the comorbidity that most patients suffered was diabetes mellitus, which was 21 people (19.4%). Conclusions: The frequency distribution of the Molecular Rapid Test (MRT) results showed that 59.3% of the MTB-detected cases were rifampicin-resistant, with 18.8% of the total. Cough with phlegm is the most common clinical symptom experienced by TB patients, namely 62%.